2014
DOI: 10.1111/evo.12522
|View full text |Cite
|
Sign up to set email alerts
|

Genome size variation affects song attractiveness in grasshoppers: Evidence for sexual selection against large genomes

Abstract: Genome size is largely uncorrelated to organismal complexity and adaptive scenarios. Genetic drift as well as intragenomic conflict have been put forward to explain this observation. We here study the impact of genome size on sexual attractiveness in the bow-winged grasshopper Chorthippus biguttulus. Grasshoppers show particularly large variation in genome size due to the high prevalence of supernumerary chromosomes that are considered (mildly) selfish, as evidenced by non-Mendelian inheritance and fitness cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
14
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 48 publications
2
14
1
Order By: Relevance
“…Although Huang et al [27] failed to find significant covariation between GS and phenotypic traits, Ellis et al [28] documented significant but environment-dependent covariation between GS and several life-history traits across a subset of these inbred lines. Schielzeth et al [29] revealed a negative association between male song attractiveness and GS in the grasshopper Chorthippus biguttulus, suggesting that sexual selection may act to reduce GS. In this species, however, variation in the number of supernumerary chromosomes (rather than more common sources of variation in GS) likely caused, or at least contributed to, the observed pattern.…”
Section: Introductionmentioning
confidence: 99%
“…Although Huang et al [27] failed to find significant covariation between GS and phenotypic traits, Ellis et al [28] documented significant but environment-dependent covariation between GS and several life-history traits across a subset of these inbred lines. Schielzeth et al [29] revealed a negative association between male song attractiveness and GS in the grasshopper Chorthippus biguttulus, suggesting that sexual selection may act to reduce GS. In this species, however, variation in the number of supernumerary chromosomes (rather than more common sources of variation in GS) likely caused, or at least contributed to, the observed pattern.…”
Section: Introductionmentioning
confidence: 99%
“…() but not by Schielzeth et al. (). This omission is important since López‐León et al.’s results are not consistent with Schielzeth et al.’s conclusion that B chromosomes are involved in sexual selection against large genomes, especially considering that the analysis of mating pairs in the field is very likely relevant to actual fitness compared to analyses of mating or courtship song in the laboratory.…”
mentioning
confidence: 86%
“…Schielzeth et al. () measured DNA content by two techniques, namely flow cytometry and a photometric approach using a Nanodrop 2000 instrument, on nuclei obtained from the isolated heads of 24 attractive and 24 unattractive males. Flow cytometry is a very accurate technique to estimate DNA content when coefficients of variation are lower than 8% (Shankey et al.…”
mentioning
confidence: 99%
“…We had recently reported an association between song attractiveness and genome size in a population of bow‐winged grasshoppers, Chorthippus biguttulus , with unattractive singers having larger genomes (Schielzeth et al. ). Camacho () commented on our publication expressing doubts whether the data support our conclusions.…”
mentioning
confidence: 99%